The adverse effects of elite competition on health and well-being - Pipe, A. (Canadian Journal of Applied Physiology, 2001)
It is often assumed that participation in sport will produce only an array of health benefits. The adverse consequences of sport participation, particularly at the elite level, are rarely explored. Evidence continues to accumulate of a variety of unfortunate consequences that may accompany elite sport participation. Sport involvement may exacerbate pre-existing health problems, cause injury or even death. The sport environment may be hazardous in a variety of physical, emotional, and social ways. The common training and competition practices of certain sport cultures may themselves be harmful. Athletes may sacrifice health, home, education and normal social development in the pursuit of sport "success." Sport medicine professionals and sport scientists have particular opportunities and responsibilities to act as an athlete's advocate--and to protect their health and well being.